y = -2x^8 + 2x^3 - 13x
y' = -16x^7 + 6x^2 - 13
y" = -112x^6 + 12x
y"(4) = -112*4096 + 12*4
= -458,752 + 48
= -458,704
2007-11-22 12:15:15
·
answer #1
·
answered by gudspeling 7
·
0⤊
0⤋
y = -2x^8 + 2x^3 -13x
y' = dy/dx(-2x^8 + 2x^3 -13x) = -16x^7 + 6x^2 - 13
y" = dy/dx(-16x^7 + 6x^2 - 13) = -112x^6 + 12x
y"(4) = -112(4)^6 + 12(4) =
-112 * 4096 + 48 = -4,58,752+48 = -458704
2007-11-22 21:15:26
·
answer #2
·
answered by A Little Sarcasm Helps 5
·
0⤊
0⤋
y = -2x^8 + 2x^3 - 13x
y' = -16x^7 + 6x^2 - 13
y" = -112x^6 + 12x
y"(4) = -112(4^6) + 12(4)
y"(4) = -458704
2007-11-22 21:43:58
·
answer #3
·
answered by Sherman81 6
·
0⤊
0⤋
y' = -16 x^7 + 6 x^2 -13
y'' = -112 x^6 + 12 x
y''(4) = -112 (4)^6 + 48 = -458704
2007-11-22 20:15:44
·
answer #4
·
answered by lhvinny 7
·
0⤊
0⤋
y'=2(8)x^7+2(3)x^2-13
y''=16(7)x^6+6(2)x
112x^6+12x
x=4
112(4^6)+12(4)
This can be simplified with a calculator.
2007-11-22 20:18:59
·
answer #5
·
answered by cidyah 7
·
0⤊
0⤋
y'=(8)(-2)x^7+(3)(2)x^2-13
= -16x^7+6x^2-13
y"=(7)(-16)x^6+(2)(6)x
= -102x^6+12x
y"(4)=-102(4)^6+12(4)
=-417.792+48
=-417.744
2007-11-22 20:27:58
·
answer #6
·
answered by bie28 4
·
0⤊
1⤋
y(4)=-112(4)^6+12*4=-458704
2007-11-22 20:16:00
·
answer #7
·
answered by SheFeltMe 3
·
0⤊
1⤋